Accelerating Climate-Resilient and Low-Carbon Development : Africa Climate Business Plan – Third Implementation Progress Report and Forward Look - World Bank (World Bank, Washington, DC, 2018)
Sub-Saharan Africa’s (SSA) race to resilience just became more urgent with the release of the IPCC 1.5°C Special Report. The Africa region must adapt to the 0.5°C warming of the past 50 years, while at the same time prepare for the intensification of climate change impacts. The good news is that the region is not starting from zero; the bad news is that the current pace of climate action is far from adequate. The Africa Climate Business Plan (ACBP) has been a galvanizing platform for climate action since its launch in December 2015, yet it must be even more ambitious in the scale and pace of climate action in the face of a new urgency to manage climate risks and deliver on climate-resilient development. Highlights of the progress up to and including FY18 as well as the main outstanding challenges are summarized here. The report also highlights successful projects that can be replicated, key lessons learned, and reflects on future strategic directions.